Development of Physics Learning Tools Model Discovery Learning on Momentum and Impulse Material - Isni Sahrianti; Muhammad Taufik; I Wayan Gunada; Aris Doyan (Postgraduate, University of Mataram, 2021)
This study aims to produce a product in the form of a learning device with a model discovery learning on momentum and impulse material. This type of research used in this study is a research and development with a research model that was developed is the model 4D comprising the steps of define, the design, development, and Disseminate. Development is carried out until the limited trial stage by conducting validation trials up to the development stage and no distribution is carried out. The tools developed were syllabus, lesson plan, student worksheet, and test instruments on momentum and impulse materials. The results of the research are based on the data obtained and the results of the data analysis show that the results of the development of learning tools have a fairly valid value, this indicates that the physics learning tools using model’s discovery learning on momentum and impulse materials are feasible to used.